DESIGN OF UNMANNED GRENADE TAMER PROTOTYPE WITH WIRELESS CONTROL - Ayip Rivai; Endro Prasetijoadi; Wawan Kusdiana; Mey Edy Prayitno (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Puslatdiksarmil is a military training and basic education center. To support the trainer in securing the grenade during the grenade throwing exercise, the author made